The Application of Headmaster’s Entrepreneurships Competence in Managing the Industrial Work Practice on Vocational High School - Muljo Rahardjo (Jurnal Pendidikan Humaniora, 2014)
Aplikasi Kompetensi Kewirausahaan Kepala Sekolah dalam Mengelola Praktik Kerja Industri pada Sekolah Menengah KejuruanAbstract: This study aimed to describe and explain the motives, procedure, approach, control and benefit applications entrepreneurial competencies of vocational high school headmaster. This study uses a qualitative approach, and multi cases design. The constant comparative method is used for the data analysis. The application motives consists of 12 items, the application procedure consists of 5 steps, a cooperative approach which consists of three items, controlling application that consists of 4 points, and the benefits of the application consists of 4 types, are the result of this study. These findings were support and complement the related theories and policies with vocational high schools.Key Words: entrepreneurship competence of headmaster, practice of industrial work, vocational schools Abstrak: Penelitian bertujuan untuk mendeskripsikan dan menjelaskan motif, prosedur, pendekatan, kontrol, dan manfaat aplikasi kompetensi kewirausahaan kepala sekolah menengah kejuruan. Penelitian menggunakan pendekatan kualitatif dan desain multikasus. Untuk analisis data, digunakan metode komparatif konstan. Hasil penelitian adalah motif aplikasi terdiri dari 12 butir, prosedur aplikasi terdiri dari 5 langkah, pendekatan kooperatif terdiri 3 butir, kontrol aplikasi terdiri dari 4 hal, dan manfaat aplikasi terdiri dari 4 tipe. Penemuan ini mendukung dan melengkapi teori-teori yang terkait dengan kebijakan sekolah menengah kejuruan.Kata kunci: kompetensi kewirausahaan kepala sekolah, praktik kerja industri, sekolah menengah kejuruan